Nutrient Alteration Drives the Impacts of Seawater Acidification on the Bloom-Forming Dinoflagellate Karenia mikimotoi - Liu, Qian; Wang, Yanqun; Li, Yuanyuan; Li, Yijun; Wang, You; Zhou, Bin; Zhou, Zhongyuan (Frontiers in Plant Science, 2021)
Seawater acidification and nutrient alteration are two dominant environmental factors in coastal environments that influence the dynamics and succession of marine microalgae. However, the impacts of their combination have seldom been recorded. A simulated experimental system was set up to mimic the effects of elevated seawater acidification on a bloom-forming dinoflagellate, Karenia mikimotoi, exposed to different nutrient conditions, and the possible mechanism was discussed. The results showed that (1) seawater acidification at different pH levels of 7.6 or 7.4 significantly influenced microalgal growth (p < 0.05) compared with the control at pH 8.0. Mitochondria, the key sites of aerobic respiration and energy production, were impaired in a pH-dependent manner, and a simultaneous alteration of reactive oxygen species (ROS) production occurred. Cytochrome c oxidase (COX) and citrate synthase (CS), two mitochondrial metabolism-related enzymes, were actively induced with seawater acidification exposure, suggesting the involvement of the mitochondrial pathway in coping with seawater acidification. Moreover, different nutrient statuses indicated by various N:P ratios of 7:1 (N limitation) and 52:1 (P limitation) dramatically altered the impacts of seawater acidification compared with those exposed to an N:P ratio of 17:1 (control), microalgal growth at pH 7.4 was obviously accelerated with the elevation of the nutrient ratio compared to that at pH 8.1 (p < 0.05), and nutrient limitations seemed beneficial for growth in acidifying conditions. The production of alkaline phosphatase (AP) and acid phosphatase (AcP), an effective index indicating the microalgal growth status, significantly increased at the same time (p < 0.05), which further supported this speculation. However, nitrate reductase (NR) was slightly inhibited. Hemolytic toxin production showed an obvious increase as the N:P ratio increased when exposed to seawater acidification. Taken together, mitochondrial metabolism was suspected to be involved in the process of coping with seawater acidification, and nutrient alterations, especially P limitation, could effectively alleviate the negative impacts induced by seawater acidification. The obtained results might be a possible explanation for the competitive fitness of K. mikimotoi during bloom development.